2008
DOI: 10.1097/aog.0b013e31816de8ad
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis for Prevention of Postpartum Perineal Wound Complications

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…A Cochrane review on antibiotic prophylaxis during OASI repair identified only one randomized control trial (RCT) [ 24 , 25 ]. Either the RCT or the Cochrane review were cited as a reference for prophylactic antibiotics at the time of repair by seven of the ten guidelines that recommended this.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review on antibiotic prophylaxis during OASI repair identified only one randomized control trial (RCT) [ 24 , 25 ]. Either the RCT or the Cochrane review were cited as a reference for prophylactic antibiotics at the time of repair by seven of the ten guidelines that recommended this.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence demonstrate that surgical antibiotic prophylaxis; defined as the administration of antibiotic prior to incision with the ultimate goal of preventing infection after surgery, significantly reduce the incidence of SSIs [8, 9]. However, the efficacy of surgical antibiotic prophylaxis depends on the following factors: choice of antibiotic, time of administration, dose, re-dosing (in prolong surgery) and duration of administration [10].…”
Section: Introductionmentioning
confidence: 99%
“… 13 Intra-operative second-generation cephalosporins have been shown to significantly reduce perineal wound infections from 24.2% to 8.2%. 14 We recommended 24–48 hours of cefazolin and metronidazole. The rates of compliance with intra- and postoperative antibiotics were all improved after implementation of the new guideline.…”
Section: Discussionmentioning
confidence: 99%